Optimization of tribological behavior of AISI 4140 under nano fly ash particulates in engine lubricating oil. (2021) - Singh, Harvinder; Singh, Anoop Kumar; Singla, Yogesh Kumar; Chattopadhyay, Kashidas; Malhotra, Reetu
Abstract: This study was conducted to find the significant design parameters that can result in low wear and friction characteristics of AISI 4140, under dispersed nano fly ash particles in engine lubricating oil (SAE 10W-30). Design of experiment was constructed using Taguchi's L9 orthogonal array approach. Tribological testing was performed using pin on disc setup according to ASTM G99-17 standard. S/N ratio with "smaller the better" was used to minimize the coefficient of friction. Experimentation to determine the effect of load (N), sliding speed (m/s), sliding distance (m) and % wt. of nano fly ash additive in engine oil was conducted using Taguchi Design Analysis & ANOVA. The analysis results depicted that the parameter % wt. of nano fly ash has highest influence on the wear characteristics. Load and sliding distance are also significant parameters affecting the friction. The predicted value of (COF) coefficient of friction at optimum levels was calculated using Taguchi optimization technique. The confirmation tests were conducted and the average value of coefficient of friction (0.0259) fell within a 95% confidence interval.